Heat, mass, and crystal growth of GaN in the ammonothermal process: A numerical study. (1st September 2016) - Mirzaee, Iman; Charmchi, Majid; Sun, Hongwei
ABSTRACT: This paper presents a computational model for the ammonothermal gallium nitride (GaN) crystal growth process, including fluid flow, heat transfer, dissolution and crystallization rates, GaN metastable phase transport, and crystal interface advancement. The presented article solves the Navier–Stokes equations along with the Brickman–Darcy–Forchheimer extensions for nutrient porous medium and Boussinesq approximation for free convection. Piecewise Linear Interface Calculation (PLIC) method is adopted to construct and advance the crystal interface. Simulations, in particular, were performed for a common research autoclave with a retrograde ammonothermal system. Special attention is given to the regions close to the crystal interface.